Is the COVID-19 vaccination a ray of hope for the elimination of prevalent infectious diseases in the future? - Tauseef Ahmad; Kaylem M. Feeney (The Egyptian Journal of Internal Medicine, 2024)
Abstract In recent years, many disease outbreaks and pandemics have been reported and have posed serious public health challenges. Therefore, vaccination on a large scale is the only hope to prevent and control these vaccine-preventable diseases. This letter discusses the COVID-19 vaccination's role in preventing other infectious diseases.